The threat of capital drain: a rationale for public banks? - Hendrik Hakenes; Isabel Schnabel (Max Planck Institute for Research on Collective Goods, 2006)
This paper yields a rationale for why subsidized public banks may be desirable from a regional perspective in a financially integrated economy. We present a model with credit rationing and heterogeneous regions in which public banks prevent a capital drain from poorer to richer regions by subsidizing local depositors, for example, through a public guarantee. Under some conditions, cooperative banks can perform the same function without any subsidization; however, they may be crowded out by public banks. We also discuss the impact of the political structure on the emergence of public banks in a political-economy setting and the role of interregional mobility.
Keywords: G21; F36; H11; L33; 330; Public banks; cooperative banks; capital drain; credit rationing; financial integration; privatization